Análise de indicadores de custo e de prazo de obras comerciais: comparação entre o planejamento e a execução - Camila Goncalves Alves Pereira (2018)
The process of planning and control of production has been put into evidence for providing improvements in the civil construction. This process allows an increase of performance in construction enterprises in terms of cost, term, quality and safety. In spite of receiving such attention, few analyses were made about both the impact of the process enforcement and the elements that affect its efficiency. Thus, the following research intends to present a comparison of the data obtained between long-term planning, budgeting stage of the enterprise, and short-term planning, execution stage of the enterprise, in six work sites located in the state of Minas Gerais. Those sites were divided into two groups (Group 01 Earthworks and Group 02 Paving/Accesses). The following work intends to evaluate the performance of the planning of industrial sites based on the indicators of deviation of cost, time and rhythm. Therefore, analyses of statistics, characteristics and behavior of each site are made. These analyses look to verify the existence of meaningful differences among the calculated indicators both in a general way and within the study groups. Correlation analyses between the indicators are developed as well as simple and multiple linear regressions. It was found a direct relation between the variables involved in the study and the influence of each indicator in the behavior of the other. The main conclusions indicate the importance of planning and control of production in the performance, efficiency and effectiveness of the enterprises.